Contributions of Ammonia-Oxidizing Archaea and Bacteria to Nitrous Oxide Production in Intensive Greenhouse Vegetable Fields - Yubing Dong; Xintong Xu; Junqian Zhang; Ying Jiao; Bingxue Wang; Chenyuan Wang; Zhengqin Xiong (Agronomy, 2023)
With excessive nitrogen (N) input, high nitrous oxide (N2O) emissions are frequently observed in greenhouse vegetable fields. We hypothesized that the underlying production mechanisms can be derived across a wide selection of vegetable fields in the middle and lower reaches of the Yangtze River. Thus, we investigated the emission characteristics and relative contributions of ammonia-oxidizing archaea (AOA) and bacteria (AOB) and other microbial processes to the N2O production from five long-term greenhouse vegetable fields through an incubation experiment with combined inhibition methods. The results showed that the ammonia oxidation process is the dominant contributor to N2O production at all five sites, accounting for 88–97% of the total N2O emissions. Regardless of acidic, neutral, or alkaline soil, AOA-driven N2O emission rates were consistently higher than AOB-driven N2O emission rates. Both AOA-driven and AOB-driven N2O emissions exhibited positive correlations with soil pH, with significant increases in soil N2O production associated with high pH levels. Therefore, general production mechanisms were derived, such that more attention should be paid to AOA-driven N2O emissions and to vegetable soils with a relatively high pH in the middle and lower reaches of the Yangtze River.